THEORETICAL BASIS OF COMPATIBILITY OF COMPLETELY-FILLED MULTICOMPONENT BINDING SYSTEMS - M. Sh. Salamanova; S. A.Yu. Murtazaev; D. K.-S. Bataev; A. Kh. Alaskhanov (Вестник Дагестанского государственного технического университета: Технические науки, 2020)
Abstract. Aim. An important direction in contemporary concrete science is aimed at the development of multicomponent systems using mineral powder fillers in a finely dispersed state to create strong and durable building composites. One of the most significant factors affecting the properties of multicomponent systems is the compatibility of its components. Efforts on the part of leading scientific institutes are aimed at replacing expensive and energy-intensive Portland cement with composite concrete products produced using mixed binders. In this context, the development of modern effective composites based on clinkerless alkaline binders becomes an urgent problem. Methods. Studies into the compatibility of multicomponent cementing systems are based on a contemporary technological approach that contributes to the production of strong and durable cement stone, without the use of traditional Portland cement. Results. Electron probe studies and X-ray phase analysis of concrete produced using a clinker-free alkaline activation binder showed that the studied multicomponent system contains a hydro-aluminosilicate zeolite phase of variable composition, as well as indicating the presence of calcite, quartz, albite feldspar, mica, zeolites and potassium feldspar. Conclusion. The results of the studies confirm the compatibility of all components of the multicomponent system comprised of mineral powder, alkaline coater and surfactant. The proposed technological method can be used to produce strong and durable building composites with clinker-free technology avoiding the use of expensive and energy-intensive Portland cement. Acknowledgments. The work was performed as part of research on the implementation of scientific project No. 05.607.21.0320. “Development of technology for new building composites on clinker-free alkaline binders using substandard natural and secondary raw materials” which received support from the federal target program “Research and Development in Priority Directions for the Development of the Russian Science and Technology Complex for 2014-2020.” Unique identifier for the agreement RFMTFI60719X0320.